Efeitos da associação do riluzol ao dantrolene em ratos submetidos ao trauma medular agudo - Bernardo de Caro Martins (2012)
The objective of this study was to evaluate the association effect of riluzole and dantrolene in the spinal cord injured rats. Twenty nine male Wistar rats, 350 g, were randomly distributed into five groups: CN (Sham), CP (Placebo), R (Riluzole, 4mg/kg), D (Dantrolene,10mg/kg) and R+D (Riluzole 4mg/kg + Dantrolene 10mg/kg). All animals underwent laminectomy of T12 and, except CN, to an acute spinal cord compressive trauma, using a stereotaxic device with a 40,5g rod for five minutes. Fifteen minutes after the laminectomy, CN, CP and D received placebo, i.p, and R, R+D, riluzole, i.p. One our after the laminectomy, CN, CP and R received placebo,i.p, and D and R+D, dantrolene,i.p. Neurologic examination, performed daily for seven days, of the animals consisted of Basso, Beatie, Bresnahan (BBB) test for the evaluation of motor function. After eight days the animals were euthanized and blood samples for hematological and biochemical analysis, and spinal cord, for histological, immunohistochemical (anti-NeuN) and TUNEL evaluation, were collected. Traumatized animals showed no ambulatory paraparesis and only the R+D group showed motor recovery after seven days of evaluation by BBB test (P<0,05). There was no statistical difference between the values of hematologic and biochemical perfils, with the exception of urea values that were higher in traumatized animals. The counting of cells stained with anti-NeuN showed a higher number of intact neurons in treated animals, mainly on those that received R+D (P<0,05). In the TUNEL technique a lower number of apoptotic cells were observed in R, D and R+D groups compared with CP. Meanwhile no diferrence in the number of apoptotic cells were observed between R+D and R, D. Acording to this results we concluded that the association of riluzole and dantrolene, 4mg/kg and 10mg/kg respectively, promoted synergistic neuroprotective effects in spinal cord injured rats, associated with improvement of motor function and decreased of the neural apoptosis.